FUNGSI AKTA NOTARIS DALAM PEMBUATAN AKTA JAMINAN FIDUSIA MENURUT UNDANG-UNDANG NOMOR 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA - Dr.Henny Saida Flora, SH.M.Hum.,M.Kn (JURNAL JUSTIQA, 2021)
The making of a Fiduciary Guarantee Deed by a Notary must be made in accordancewith the existing laws and regulations. In practice, notaries often make mistakes bymaking a fiduciary guarantee deed that exceeds the amount that is limited to making thedeed as it should be and then the notary also often makes a fiduciary guarantee deedoutside the notary's jurisdiction, whereas if the notary acts outside his jurisdiction, thedeed can be filed for cancellation. by parties who have an interest in the general courtand there has been a general court decision that has permanent legal force or thenotarial deed has a proving position as a private deed or a notarial deed is null and void.